ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PENCATATAN NIKAH PADA KANTOR URUSAN AGAMA KECAMATAN MURUNG PUDAK (p3m.stiatabalong.ac.id, 2022)
In implementing public services, some factors influence each other on the quality of service, and these factors can be a consideration for service providers to improve service quality. The purpose of the study was to determine and analyze the factors that influence the service of marriage registration at the Office of Religious Affairs, Murung Pudak District. The study used quantitative descriptive methods. The research was conducted at the Office of Religious Affairs, Murung Pudak District. The population in this study was the entire community who received marriage registration services at the Office of Religious Affairs, Murung Pudak District. The number of samples in this study was 30 people using the Accidental Sampling technique, which consisted of 1 Head of Office, four employees, and 25 people who received marriage registration services at the Office of Religious Affairs, Murung Pudak District. Data collection techniques using observation, questionnaires, and documentation studies. The primary data collection instrument used a closed questionnaire distributed to all samples using the Guttman scale as the measurement scale. Data analysis used quantitative descriptive techniques using percentages. The results of the research conducted indicate that the factors that influence the quality of marriage registration services at the Office of Religious Affairs, Murung Pudak District, are physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), competence, friendliness (courtesy), trust (credibility). ), security (security), access (access), communication (communication), and understanding the customer (understanding the customer). Keywords: Service Quality, Marriage Registration